Public key cryptosystem in finite field (GF(2^n)) utilizing digital signal processors and fast fourier transform techniques - Ortiz, Noli E. (1998)
This thesis involve the development, simulation and testing of a DSP-based, ElGamal Public Key Cryptosystem (PKC). PKC's are used to provide security and privacy to data communication systems including data storage and retrieval systems. Current implementations of PKC's are either slow or requires expensive hardware or custom VLSI. PCK in Galois field GF(2 to the n) utilizing digital signal processors (DSPs) and fast Fourier transform (FFT) techniques offers an efficient alternative to current implementations, especially so for countries where VLSI technology is not yet mature. The DSP-FFT-based PKC in GF(2 to the 1024) was implemented using Motorola's DSP560000.
Computer print-out.
Thesis (M.S.)--University of the Philippines, Diliman.
Keywords: Ciphers; Computer security; Cryptography; Data protection